Divergent dual C-H isotopic fractionation pattern during anaerobic biodegradation of toluene within Aromatoleum species under nitrate-reducing conditions - Maria Pinel-Cabello; Kenneth Wasmund; Jesica M. Soder-Walz; Maria Vega; Mònica Rosell; Ernest Marco-Urrea (Environmental Pollution, 2024)

Respiratory protein interactions in Dehalobacter sp. strain 8M revealed through genomic and native proteomic analyses - Jesica M. Soder‐Walz; Kenneth Wasmund; Darja Deobald; Teresa Vicent; Lorenz Adrian; Ernest Marco‐Urrea (Environmental Microbiology, 2023)
Dehalobacter ( Firmicutes ) encompass obligate organohalide‐respiring bacteria used for bioremediation of groundwater contaminated with halogenated organics. Various aspects of their biochemistry remain unknown, including the identities and interactions of respiratory proteins. Here, we sequenced the genome of Dehalobacter sp. strain 8M and analysed its protein expression. Strain 8M encodes 22 reductive dehalogenase homologous (RdhA) proteins. RdhA D8M_v2_40029 (TmrA) was among the two most abundant proteins during growth with trichloromethane and 1,1,2‐trichloroethane. To examine interactions of respiratory proteins, we used blue native gel electrophoresis together with dehalogenation activity tests and mass spectrometry. The highest activities were found in gel slices with the highest abundance of TmrA. Protein distributions across gel lanes provided biochemical evidence that the large and small subunits of the membrane‐bound [NiFe] uptake hydrogenase (HupL and HupS) interacted strongly and that HupL/S interacted weakly with RdhA. Moreover, the interaction of RdhB and membrane‐bound b‐ type cytochrome HupC was detected. RdhC proteins, often encoded in rdh operons but without described function, migrated in a protein complex not associated with HupL/S or RdhA. This study provides the first biochemical evidence of respiratory protein interactions in Dehalobacter , discusses implications for the respiratory architecture and advances the molecular comprehension of this unique respiratory chain.

Proteogenomics of the novel Dehalobacterium formicoaceticum strain EZ94 highlights a key role of methyltransferases during anaerobic dichloromethane degradation - Kenneth Wasmund; Alba Trueba-Santiso; Teresa Vicent; Lorenz Adrian; Stéphane Vuilleumier; Ernest Marco-Urrea (Environmental Science and Pollution Research, 2023)
Dichloromethane (DCM, methylene chloride) is a toxic, high-volume industrial pollutant of long-standing. Anaerobic biodegradation is crucial for its removal from contaminated environments, yet prevailing mechanisms remain unresolved, especially concerning dehalogenation. In this study, we obtained an assembled genome of a novel DCM-degrading strain, Dehalobacterium formicoaceticum strain EZ94, from a stable DCM-degrading consortium, and we analyzed its proteome during degradation of DCM. A gene cluster recently predicted to play a major role in anaerobic DCM catabolism (the mec cassette) was found. Methyltransferases and other proteins encoded by the mec cassette were among the most abundant proteins produced, suggesting their involvement in DCM catabolism. Reductive dehalogenases were not detected. Genes and corresponding proteins for a complete Wood-Ljungdahl pathway, which could enable further metabolism of DCM carbon, were also found. Unlike for the anaerobic DCM degrader “ Ca . F. warabiya,” no genes for metabolism of the quaternary amines choline and glycine betaine were identified. This work provides independent and supporting evidence that mec -associated methyltransferases are key to anaerobic DCM metabolism.

Microbial communities and processes in biofilters for post-treatment of ozonated wastewater treatment plant effluent - Daniel Sauter; Andrea Steuer; Kenneth Wasmund; Bela Hausmann; Ulrich Szewzyk; Alexander Sperlich; Regina Gnirss; Myriel Cooper; Thomas Wintgens (Science of The Total Environment, 2023)

Bacterial interactions during sequential degradation of cyanobacterial necromass in a sulfidic arctic marine sediment - Albert L. Müller; Claus Pelikan; Julia R. de Rezende; Kenneth Wasmund; Martina Putz; Clemens Glombitza; Kasper U. Kjeldsen; Bo Barker Jørgensen; Alexander Loy (Environmental Microbiology, 2018)
Summary Seafloor microorganisms impact global carbon cycling by mineralizing vast quantities of organic matter (OM) from pelagic primary production, which is predicted to increase in the Arctic because of diminishing sea ice cover. We studied microbial interspecies‐carbon‐flow during anaerobic OM degradation in arctic marine sediment using stable isotope probing. We supplemented sediment incubations with 13 C‐labeled cyanobacterial necromass (spirulina), mimicking fresh OM input, or acetate, an important OM degradation intermediate and monitored sulfate reduction rates and concentrations of volatile fatty acids (VFAs) during substrate degradation. Sequential 16S rRNA gene and transcript amplicon sequencing and fluorescence in situ hybridization combined with Raman microspectroscopy revealed that only few bacterial species were the main degraders of 13 C‐spirulina necromass. Psychrilyobacter, Psychromonas, Marinifilum, Colwellia, Marinilabiaceae and Clostridiales species were likely involved in the primary hydrolysis and fermentation of spirulina. VFAs, mainly acetate, produced from spirulina degradation were mineralized by sulfate‐reducing bacteria and an Arcobacter species. Cellular activity of Desulfobacteraceae and Desulfobulbaceae species during acetoclastic sulfate reduction was largely decoupled from relative 16S rRNA gene abundance shifts. Our findings provide new insights into the identities and physiological constraints that determine the population dynamics of key microorganisms during complex OM degradation in arctic marine sediments.© 2018 Society for Applied Microbiology and John Wiley & Sons Ltd

Development and application of primers for the class D ehalococcoidia (phylum C hloroflexi ) enables deep insights into diversity and stratification of subgroups in the marine subsurface - Kenneth Wasmund; Camelia Algora; Josefine Müller; Martin Krüger; Karen G. Lloyd; Richard Reinhardt; Lorenz Adrian (Environmental Microbiology, 2015)
Summary Bacteria of the class D ehalococcoidia ( DEH ) (phylum C hloroflexi ) are widely distributed in the marine subsurface and are especially prevalent in deep marine sediments. Nevertheless, little is known about the specific distributions of DEH subgroups at different sites and depths. This study therefore specifically examined the distributions of DEH through depths of various marine sediment cores by quantitative PCR and pyrosequencing using newly designed DEH 16 S rRNA gene targeting primers. Quantification of DEH showed populations may establish in shallow sediments (i.e. upper centimetres), although as low relative proportions of total Bacteria , yet often became more prevalent in deeper sediments. Pyrosequencing revealed pronounced diversity co‐exists within single biogeochemical zones, and that clear and sometimes abrupt shifts in relative proportions of DEH subgroups occur with depth. These shifts indicate varying metabolic properties exist among DEH subgroups. The distributional changes in DEH subgroups with depth may be related to a combination of biogeochemical factors including the availability of electron acceptors such as sulfate, the composition of organic matter and depositional regimes. Collectively, the results suggest DEH exhibit wider metabolic and genomic diversity than previously recognized, and this contributes to their widespread occurrence in the marine subsurface.